Evaluasi Penyimpanan Obat di Instalasi Farmasi Rumah Sakit Umum GMIM Kalooran amurang Kabupaten Minahasa Selatan - Karlah Frylina Kantu; Gayatri Citraningtyas; Imam Jayanto (UNIVERSITAS SAM RATULANGI, 2023)
Depository is a significant stage in medicine administration. A great depository guarantees safety and maintains medicine quality. Hence, it can minimize hospitalâ€™s losses caused by spoiled medications. This study aimed to evaluate the medicine depository at GMIM Kalooran Hospital in Amurang. This study employed descriptive observational methods, and data gathering techniques used direct observation to existing systems and interviews. Study findings indicated that medicine Depository at Pharmacy Installation of GMIM Kalooran Hospital in Amurang not was in accordance with the standard of Hospitals pharmaceutical treatment based on Health Regulation number 72 (2016), Director General of Pharmaceutical (2010). However, facilities and infrastructures still required improvements such as insufficient shelves and pallets due to inadequate sizes of warehouses and no installed security systems.Â It is highly recommended to notice matters which are not in accordance with the standardized indicators of medicine depository as well as the defective and incompetent facilities.